Morphological evolution in the graminid clade: Comparative floral anatomy of the grass relatives Flagellariaceae and Joinvilleaceae - Sajo, M. Graça [UNESP]; Rudall, Paula J. (Oxford University Press (OUP), 2012)
New comparative data are presented on the reproductive morphology and anatomy of two genera closely related to grasses, Flagellaria and Joinvillea, in which the flowers are superficially similar, especially in stamen morphology. This investigation demonstrates some anatomical differences between the two genera. For example, both genera depart from the 'typical' condition of tepal vasculature (three-traced outer tepals and one-traced inner tepals): in Flagellaria, each tepal receives a single vascular bundle and, in Joinvillea, each tepal is supplied by three vascular bundles. Joinvillea possesses supernumerary carpel bundles, as also found in the related family Ecdeiocoleaceae, but not in Flagellaria or grasses. In the anther, the tapetum degenerates early in Flagellaria, and is relatively persistent in Joinvillea, in which the pollen grains remain closely associated with the tapetum inside the anther locule, indicating a correlation between peripheral pollen (a feature that is common in grasses) and a persistent tapetum. This study highlights the presence of a pollen-tube transmitting tissue (PTTT) or solid style in the gynoecium of Flagellaria, as also in many Poaceae, but not in Joinvillea or Ecdeiocoleaceae. We speculate that the presence of a PTTT could represent one of the factors that facilitated the subsequent evolution of the intimately connected gynoecia that characterize grasses. © 2012 The Linnean Society of London.
Keywords: Anther wall; Carpel; Caryopsis; Ecdeiocoleaceae; Flagellaria; Floral evolution; Joinvillea; Tapetum; Vasculature; anatomy; cladistics; climbing plant; comparative study; evolutionary biology; flower; morphology; phylogeny; pollen; reproductive biology; taxonomy; Flagellariaceae; Joinvilleaceae; Poaceae